Estudo experimental e simulação de fontes de ruído aerodinâmico veicular - Wagner Duarte Machado (2016)
The internal acoustic comfort has become a fundamental requirement in modern production vehicles around the world. In this context, the reduction of aerodynamic noise is an important aspect to be considered, since the other sources of noise such as powertrain assembly, tires,exhaust system and intake system have been constantly attenuated. Considering the sources of aerodynamic noise in a vehicle, the buffeting is one of the most important. Within the vehicle aerodynamic noise, buffeting refers to the type of noise that is characterized by pressurefluctuations inside the vehicle when it is in motion with the windows open. This noise causes considerable discomfort to internal occupants and occurs at extremely high levels and at low frequencies. Likewise, the aerodynamic noise generated by the side mirror and the A-pillaralso deserves special attention, since these sources are close to the ears of the driver, so they are easily noticed when the noise levels generated are high or even have tonal characteristics. For these reasons, these sources of aerodynamic noise were studied in this thesis.Experimental tests methodologies of aerodynamic noise were developed on a vehicle, using both a wind tunnel and on a track. It developed, in part, a methodology of experimental tests to study and understand the buffeting phenomenon, in which it was possible to confirm thehypothesis that buffeting generation mechanism may be associated with resonance due to coupling of the excitation frequency of the air flow at the opening to the acoustic frequency of the cavity mode, the same phenomenon that occurs in an open cavity. Complementary, anumerical simulation using computational fluid dynamics (CFD) was developed to predict aerodynamic noise at the same noise sources that are focused on in this research work. Validation of the numerical simulation was confirmed by experimental results. Finally, correlation was established by comparing results obtained in the wind tunnel tests with the tests conducted in the road under the same operating conditions of the vehicle. This correlation led to the understanding of the limitations of the wind noise tests on the road, making this feature a reliable alternative also for aerodynamic noise measurements, since wind tunnel laboratories are not readily available.